Hong Kong in the Belt and Road initiative - Kin-chung, Lam; Cai, Chimeng, 1962-; Dai, Jinping; Li, Xiaohui, 1955-; Sing, Lee Woo (The Chinese University of Hong Kong Press, 2020)
This monograph is completed with the efforts of some 20 experts from both Hong Kong and the Chinese Mainland, it is literally a "concise encyclopaedia" of Hong Kong in the "Belt and Road." It provides a comprehensive introduction to the national initiative; exploring various opportunities for the territory in the "Belt and Road," as well as Hong Kong's cooperation with relevant regions along the routes, including ASEAN, Europe, the Shanghai Cooperation Organization and Arab states.